Are bio-based and biodegradable microplastics impacting for blue mussel (Mytilus edulis)?. (June 2021) - Khalid, Amina; Zalouk-Vergnoux, Aurore; Benali, Samira; Mincheva, Rosica; Raquez, Jean-Marie; Bertrand, Samuel; Poirier, Laurence
Abstract: The substitution of petrochemical plastics by bio-based and biodegradable plastics are in need of an evaluation for the potential toxic impacts that they can have on marine wildlife. This study aims to assess the toxicological effects of polylactic acid microparticles at two concentrations, 10 and 100 μg/L, during 8 days on the blue mussel, Mytilus edulis . No significant oxidative stress (catalase, glutathione-S-transferase and superoxide dismutase activities), neurotoxicity (acetylcholinesterase), or immunotoxicity (lysosomal membrane stability and acid phosphatase activity) were detectable. The multivariate analysis of metabolomic data allowed us to differentiate the individuals according to the exposure. From the loading plot of OPLS-DA, 48 ions down-regulated in the individuals exposed to microplastics. They were identified based on HRMS data as glycerophospholipids. Highlights: Mytilus edulis were exposed to bio-based and biodegradable fragments from 0.8 to 10 μm and at 10 and 100 μg/L for 8 days. No significant oxidative stress, neurotoxicity and immunotoxicity were reported. Mussels exposed to microplastics were differentiated from controls, thanks to the metabolomic approach. 48 ions were down-regulated in the mussels exposed to microplastics according to the multivariate analysis of metabolomics. Biochemical and metabolomic approaches in ecotoxicology are complementary.